Study of fetomaternal outcome in eclampsia - Agarwal, Manju; Gautam, Akanksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Eclampsia is a life-threatening emergency that continues to be a major cause of maternal and perinatal mortality. The purpose of our study was to analyse the trend of eclampsia in a tertiary care teaching institute and to find out the fetomaternal outcomes of eclampsia. Methods: A retrospective epidemiological study was undertaken in the department of Obstetrics and Gynaecology, Jhalawar medical college, Jhalawar during the period ‘September 2018 to August 2019’. Women who presented as eclampsia or developed eclampsia during hospital stay were included in the study. Data analysed included various maternal parameters, fetal parameters, and the outcome of the pregnancy. Results: The incidence of antepartum eclampsia was (0.92%). High risk associated factors were primigravida (65.90%), low maternal age (21-30 years), illiteracy, and inadequate antenatal care. Caesarean section was the mode of delivery in 48 cases (54.54%) most common indication was unfavourable cervix, 80.6% women had antepartum eclampsia and 68.18% women had severe preeclampsia. There was 6.8% maternal mortality, attributed to pulmonary edema and acute renal failure. Perinatal mortality was 14.77% with 8 still births and 5 neonatal deaths. Prematurity complicated 46.66% pregnancies. Thirty neonates were admitted to NICU. Conclusions: Eclampsia is one of the important causes of maternal and perinatal morbidity and mortality due to lack of proper antenatal care, low socio-economic status, and lack of education. It can be concluded that better antenatal care, early recognition of disease, timely referral, early initiation of treatment and termination of eclamptic patients improves outcome. Management of eclamptic patients should be performed at tertiary care centres, where ICU facilities, NICU facilities, and multidisciplinary units are available.